Natural and Positive Law in the Concept of Correcting Offenders - Tatiana L. Shklyar3Elena G. Bagreeva1, Alexander S. Blankov2, (Opción, 2019)
The aim of the study is to investigate natural and positive law in the concept of correcting offenders via comparative qualitative research methods. As a result, the actual task for the modern prison systems is not only serving the sentence in a safe environment, but also to help convicts to be ready for successful resocialization, as prevention of recurrence on the basis of norms of natural and positive law. In conclusion, implementation of the proposed penal concept of criminal reform will require, in practice, its deeper comprehension, understanding of the mechanisms and prerequisites of its implementation.